2020
DOI: 10.1007/s42452-020-2681-8
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the effect of concrete composition on rebar–concrete interface (RCI) bond strength: A case study of nanoparticles

Abstract: Minimum concrete cover for rebar, rebar diameter, concrete compressive strength, embedded length of rebar, and lateral reinforcement by stirrups are the crucial factors considered in existing predicting equations and regulations for predicting rebar-concrete interface (RCI) bond strength. However, considerable effects of concrete composition on RCI are ignored in design codes and investigations. This paper intends to comprehensively highlight the critical aspects of this research gap. Additionally, a practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 159 publications
1
10
0
Order By: Relevance
“…Previous studies reported that concrete composition significantly affects the bond strength between reinforcing bar (rebar) and surrounding concrete [170,171]. A few researchers have studied the effect of clays on the bond strength of reinforcing bars in the surrounding concrete.…”
Section: Bond Strengthmentioning
confidence: 99%
“…Previous studies reported that concrete composition significantly affects the bond strength between reinforcing bar (rebar) and surrounding concrete [170,171]. A few researchers have studied the effect of clays on the bond strength of reinforcing bars in the surrounding concrete.…”
Section: Bond Strengthmentioning
confidence: 99%
“…Nanotechnology is a research area that has revolutionized the mechanical and chemical properties of materials [125,126]. Nanotechnology is a promising research field with applications to improve the quality of the product and the performance of concretes [127].…”
Section: Nano Alumina (Na) Applications In Sccmentioning
confidence: 99%
“…The concrete composition considerably impacts concrete's mechanical and durability characteristics 1 , 2 . Despite the mechanical properties, understanding the effect of concrete composition on durability is still challenging for researchers in this field 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these variables, concrete composition plays a major role in controlling internal damage of chloride attack. Previous studies strongly emphasized that concrete composition directly affects the fresh, mechanical, and durability characteristics 2 , 5 . Concrete composition means the water-to-binder ratio (W/B), water content, cement content, cement type, aggregate content, aggregate type, fillers, nanomaterials, mineral additives, and chemical admixtures.…”
Section: Introductionmentioning
confidence: 99%